Acoustic and In‐Situ Observations of Deep Seafloor Hydrothermal Discharge: An OOI Cabled Array ASHES Vent Field Case Study. Issue 3 (1st March 2021) - Xu, Guangyu; Bemis, Karen; Jackson, Darrell; Ivakin, Anatoliy
Abstract: The Cabled Observatory Vent Imaging Sonar (COVIS) was installed on the Ocean Observatories Initiative's Regional Cabled Array observatory at ASHES hydrothermal vent field on Axial Seamount in July 2018. The acoustic backscatter data recorded by COVIS in August–September 2018, in conjunction with in situ temperature measurements, are used to showcase and verify the use of COVIS for long‐term, quantitative monitoring of hydrothermal discharge. Specifically, sonar data processing generates three‐dimensional backscatter images of the buoyant plumes above major sulfide structures and two‐dimensional maps of diffuse flows within COVIS's field‐of‐view. The backscatter images show substantial changes of plume appearance and orientation that mostly reflect plume bending in the presence of ambient currents and potentially the variations of outflow fluxes. The intensity of acoustic backscatter decreases significantly for highly bent plumes as compared to nearly vertical plumes, reflecting enhanced mixing of plume fluids with seawater driven by ambient currents. A forward model of acoustic backscatter from a buoyancy‐driven plume developed in this study yields a reasonable match with the observation, which paves the way for inversely estimating the source heat flux of a hydrothermal plume from acoustic backscatter measurements. The acoustic observations of diffuse flows show large temporal variations on time scales of hours to days, especially at tidal frequencies, but no apparent long‐term trend. These findings demonstrate COVIS's ability to quantitatively monitor hydrothermal discharge from both focused and diffuse sources to provide the research community with key observational data for studying the linkage of hydrothermal activity with oceanic and geological processes. Key Points: An observatory imaging sonar provides time‐series observations of hydrothermal discharge from both focused and diffuse sources at ASHES Acoustic observations of focused and diffuse flows show variations largely modulated by bottom currents A plume backscatter model is developed and yields results that are consistent with observations